FITUR-FITUR FONOLOGIS PENGGUNAAN ELEMEN-ELEMEN BAHASA ARAB DALAM KOMUNIKASI MASYARAKAT KETURUNAN ARAB SURAKARTA - Jiah Fauziah (Sunan Kalijaga State Islamic University Yogyakarta, 2011)
This qualitative research is aimed at describing the phonological features of the Arabic elements used in the communication of the Arabic migrant community of Surakarta. It is assumed that the long contact with Austronesian languages, i.e. Indonesian and Javanese, as languages of the majority gives significant influence on the language they maintain from their ancestors. The main data are the lexicon list of the Arabic elements used in the community, and the supporting data are the system of classical/ standard Arabic and information on their ancestors’ Arabic dialect as a comparison. To get the lexicon data of the Arabic in Surakarta, the interview is done, whereas the data of the system of Classical Arabic and the ancestors’ dialect are gathered using interview and library research methods. In the analysis, the writer applies comparative method using the theory of language change. After examining closely and analyzing the data, the writer comes to a conclusion that the Arabic language elements used in the Arabic migrant group in Surakarta has undergone several phonological modifications in which most of the features show strong influences of the language of the majority, and some shows the modification of their ancestors’ dialect.